Felts - Dwojak, Adam (Instal, 2022)
The article discusses the issue of using felt inserts in impulse pipeline supervision pre-insulated systems. Contrary to the emerging opinion that there may be a renaissance of such systems, it seems to be unlikely, and the argument about better recognition of such a place on the reflectometric graph is insufficient.